Comparison of the Oral Health‐Related Quality of Life, Sleep Quality, and Oral Health Literacy in Sleep and Awake Bruxism: Results from Family Medicine Practice - Melike Mercan Başpınar; Çiğdem Mercan; Metin Mercan; Merve Arslan Aras (International Journal of Clinical Practice)
Objectives. Bruxism is a common oral behaviour. This study aimed to compare oral health‐related quality of life, sleep quality, and oral health literacy in patients with and without possible sleep bruxism (SB) and awake bruxism (AB). Materials and Methods. A cross-sectional study including 249 volunteers was conducted in a family medicine clinic of a tertiary hospital in Istanbul, Turkey. The American Sleep Medicine Association Bruxism Diagnostic Criteria, Pittsburgh Sleep Quality Index (PSQI), Oral Health-Related Quality of Life (OHRQoL) tool, Decay Missing Filled Total Teeth (DMFT) score, and Health Literacy Dental Scale-Short Form (HeLD-14) were assessed by face-to-face interviews. Data were examined using Kruskal–Wallis and Mann–Whitney U tests, Spearman correlation, and logistic regression analysis. Results. The presence of SB and AB was detected as 41.4% and 21.7%, respectively, among 91 males and 158 females, with a mean age of 36.64 ± 11.60 years. Sleep and awake bruxers had a lower oral health-related quality of life (odds ratio (OR): 0.816, 95% confidence interval (CI) = 0.770–0.864 and OR: 0.923, 95% CI = 0.956–0.982, respectively). Poor sleep quality was detected 1.28 times higher in sleep bruxism (OR: 1.277, 95% CI = 1.152–1.415) and 1.14 times higher in awake bruxism (OR: 1.141, 95% CI = 1.230−1.058). The DMFT score was found to be 1.13 times higher in SB (OR: 1.129, 95% CI = 1.043–1.223). A higher HeLD-14 score was associated with a lower DMFT score (p<0.001; r = −0.240). The oral health literacy score was lower in AB and SB groups than in patients without bruxism, but it was not statistically significant (p=0.267, p=0.376). Conclusion. A lower oral health-related quality of life and poor sleep quality would be expected in the presence of SB or AB. However, patients may not be aware of it unless asked by a physician regardless of oral health literacy level.